Preventing termite damage to buildings - safely and cheaply - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
In the tropics, termites are major pests of buildings such as offices and stores. Buildings of traditional construction may have to be replaced every 3-9 years; grain stores may need replacing annually. Entire villages have had to be relocated...